Experimental study and analysis on fatigue stiffness of RC beams strengthened with CFRP and steel plate - Lu, Yi-yan; Hu, Ling; Li, Shan; Wang, Kang-hao (Journal of Central South University, 2016)
The objective of this work is to investigate the fatigue behavior of reinforced concrete (RC) beams strengthened with externally bonded carbon fiber reinforced polymer (CFRP) and steel plate. An experimental investigation and theoretical analysis were made on the law of deflection development and stiffness degradation, as well as the influence of fatigue load ranges. Test results indicate that the law of three-stage change under fatigue loading is followed by both midspan deflection and permanent deflection, which also have positive correlation with fatigue load amplitude. Fatigue stiffness of composite strengthened beams degrades gradually with the increasing of number of cycles. Based on the experimental results, a theoretical model by effective moment of inertia method is developed for calculating the sectional stiffness of such composite strengthened beams under fatigue loading, and the calculated results are in good agreement with the experimental results.